Fundacja rodzinna w Polsce w świetle jej odpowiedzialności za zobowiązania fundatora – uwagi wstępne na tle ustawy z dnia 26 stycznia 2023 roku - Biały, Aneta (PRAWO i WIĘŹ, 2025)
Introduction of a new institution into the Polish legal system, i.e. a family foundation, following the example of foreign legislation, can be considered as a nod of the legislator towards maintaining the continuity of family assets, building the position of the family from generation to generation, and maintaining multi-generational assets. In this direction, the founder’s achievements are to be accumulated in a family foundation established by him, the beneficiaries of which are, by assumption, people belonging to the founder’s family. It seems, however, as the author will try to demonstrate, that not all the regulations contained in this still new act have been thought through by the legislator, which in practice may give rise to a number of complications. The author focused on an extremely important part of the act relating to the issue of the family foundation’s liability for the founder’s obligations. This topic is important because the scope of the foundation is limited to the amount of assets contributed by the founder, but it applies to all due and undue liabilities. Since a family foundation is supposed to provide security for its beneficiaries, especially in terms of maintenance and education, the funds for this purpose must be adequately secured. Perhaps the minimum value of property contributed by the founder to the foundation, set at PLN 100,000.00, is intended to provide this security. However, if we pay attention to the basic goals of the foundation, firstly, this amount is not high, although on the other hand it may be an obstacle to overcome for some potential founders, and if we add the responsibility for the founder’s debts, it may quickly turn out that that the idea of a foundation cannot be implemented in a specific case. Perhaps it would be worth it, at the stage of creating regulations, to oblige the founder to submit a financial report to the founding act, which would clearly indicate the financial condition, which would in turn allow for a greater chance of achieving the main goal set by the legislator.